Force-displacement distributions and percolation properties in simulated 2-D packings - Vidales, Ana Maria (2003)
The first part of this paper studies the behavior of contact force distributions and displacement distributions in isostatic 2-D arrays of polydispersed grains as a function of force strength and displacement strength, respectively. The array is built by pouring disks, one by one, into a rectangular die. After the array is ready, force and displacement measurements are performed on it. We also introduce a relaxation procedure (rearrangements of disks) in order to study the behavior of the corresponding distributions as a function of the number of relaxations performed on the system. In the second part, we characterize the percolation of small particles through this 2-D packings as a function of the polydispersivity of the disks. We analyze both trapping and non-trapping regimes. Characteristic features of these packings are discussed.